2006
DOI: 10.1111/j.1440-6055.2006.00556.x
|View full text |Cite
|
Sign up to set email alerts
|

Refining the process of agent selection through understanding plant demography and plant response to herbivory

Abstract: Understanding plant demography and plant response to herbivory is critical to the selection of effective weed biological control agents. We adopt the metaphor of 'filters' to suggest how agent prioritisation may be improved to narrow our choices down to those likely to be most effective in achieving the desired weed management outcome. Models can serve to capture our level of knowledge (or ignorance) about our study system and we illustrate how one type of modelling approach (matrix models) may be useful in id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 84 publications
1
42
0
Order By: Relevance
“…For novel programs, it would be economically prudent to release fewer agents if the cost of developing several agents outweighs the cost of a more rigorous agent selection process that aims to select only the best agent or best combination of agents. Improving agent selection has been a long-term goal of weed biocontrol research (e.g., Goeden, 1983;Harris, 1973;Raghu et al, 2006;Sheppard, 2003;Van Klinken and Raghu, 2006) and some progress has been made, for example, Paynter et al (2010) demonstrated how to select biocontrol agents that are more likely to escape attack from parasitoids. Nevertheless, more work is required to determine whether the likelihood of predation or disease can similarly be predicted and, if so, what the population level impacts are likely to be (Fowler et al, 2012).…”
Section: Program Typementioning
confidence: 98%
“…For novel programs, it would be economically prudent to release fewer agents if the cost of developing several agents outweighs the cost of a more rigorous agent selection process that aims to select only the best agent or best combination of agents. Improving agent selection has been a long-term goal of weed biocontrol research (e.g., Goeden, 1983;Harris, 1973;Raghu et al, 2006;Sheppard, 2003;Van Klinken and Raghu, 2006) and some progress has been made, for example, Paynter et al (2010) demonstrated how to select biocontrol agents that are more likely to escape attack from parasitoids. Nevertheless, more work is required to determine whether the likelihood of predation or disease can similarly be predicted and, if so, what the population level impacts are likely to be (Fowler et al, 2012).…”
Section: Program Typementioning
confidence: 98%
“…The interrelationship between the invasive plant, the invaded ecosystem, and the biological control agent can be used to test key hypotheses in ecology, such as the role of top-down versus bottom-up regulation of vegetation composition, or the likelihood and rate of ecosystem recovery in relation to the ecosystem property affected by plant invasions. Much has been learned in the past few decades about the effect of specialist herbivores on plant population dynamics from biological control programmes (Briese 2000;Myers and Bazely 2003;Sheppard et al 2003;Briese 2004;Raghu et al 2006). Recently, it is increasingly acknowledged that plant invasions and classical biological control programmes are also great models with which to study evolution (Lee 2002;Bossdorf et al 2005).…”
Section: Studies Towards Integrative Biological Controlmentioning
confidence: 99%
“…Any weed biocontrol program needs to get at the population dynamics of the target weed, itself influenced by climate, and how feeding impacts on its abundance (e.g. Kriticos et al 1999;Buckley et al 2003Buckley et al , 2004Buckley et al , 2005Kriticos 2003;Raghu et al 2006). …”
Section: Introductionmentioning
confidence: 99%